2015
DOI: 10.1016/j.jbankfin.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing competition in the banking industry: A multi-product approach

Abstract: This paper investigates the competitive aspects of multi-product banking operations. Extending Panzar and Rosse (1987)'s model to the case of a multi-product banking firm, we show that the higher the economies of scope in multi-product banking are, the lower Panzar-Rosse's measure of competition in the banking sector is. To test this empirical implication and determine the impact of multi-production/conglomeration on market power, we use a new dataset on Brazilian banking conglomerates. Consistent with our the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
4
37
0
3
Order By: Relevance
“…We provided empirical evidence that the Brazilian banking sector does not operate under competition, contrary to the fi ndings provided by those authors. Recently, Barbosa et al (2015) also found evidence of high market power in the banking sector after taking into account the multi-product structure of the Brazilian banks. For further research, one should evaluate the effi ciency of distinct seasonal adjustment methods applied to fi nancial series, compute the Lerner Index, and extend the discussion on how the normalization of input prices might generate alternative ways of working with the PanzarRosse model.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We provided empirical evidence that the Brazilian banking sector does not operate under competition, contrary to the fi ndings provided by those authors. Recently, Barbosa et al (2015) also found evidence of high market power in the banking sector after taking into account the multi-product structure of the Brazilian banks. For further research, one should evaluate the effi ciency of distinct seasonal adjustment methods applied to fi nancial series, compute the Lerner Index, and extend the discussion on how the normalization of input prices might generate alternative ways of working with the PanzarRosse model.…”
Section: Discussionmentioning
confidence: 95%
“…The differences among the results are due to methodological aspects that need to be further developed by incorporating the Bikker, Spierdijk, and Shaffer (2012) criticism and dispensing appropriate treatments to the fi nancial series involved in the estimation. Recently, Barbosa et al (2015) also found evidence of a non-competitive market structure through the estimation of a negative adjusted H-statistic. They extend the Panzar and Rosse's (1987) model to the case of a multi-product banking fi rm and argue that the market power of Brazilian banks is positively associated to the multi-product structure of banks.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lucinda (2010) não encontrou evidência de colusão perfeita, L. S. Alencar (2011) encontrou evidência de que a consolidação no setor bancário impactou o nível de spreads e Nakane & Rocha (2010) concluíram haver razoável nível de competição no mercado bancário brasileiro. Barbosa, Rocha & Salazar (2015) e Barbosa, Cardoso & Azevedo (2016), no entanto, alertaram para a existência de viés de superestimação da intensidade de concorrência bancária. L. Alencar, Andrade & Barbosa (2017) concluíram que a falta de competição no mercado bancário diminui o potencial de redução de spread bancário que é propiciado por reformas que melhoram os níveis de enforcement contratual.…”
Section: O Problema Dos Spreads Bancários No Brasilunclassified
“…Also according to Vender Vennet (2002) the higher efficiency level of omni-product banks (in compare of traditional banks) contains revenue and profit. He shows that economies of scope in these poly-product banks is essentially the cause to an efficiency success (Barbosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%